Intercropping pulses with mulberry on sericulture productivity and profitability (Bangladesh Journal of Agriculture, 2023)
This study was conducted during 2020-2021 in three locations viz: research field of Bangladesh Sericulture Research and Training Institute (BSRTI), Rajshahi, five farmer’s fields of Bholahat, Chapainawabganj and Paba, Rajshahi to evaluate the effect of growing pulses intercrops with mulberry productivity, silkworm rearing, soil properties and economy. The experiments were laid out in RCBD methods with three replications and six treatments.The growth and yield parameters of mulberry like average branch number/plant, total leaf number/plant, total branches length/plant, nodes/ meter/plant, length of longest shoot, leaf present/branch, 10 leaves area, total leaf weight/plant, total shoots weight/plant and total leaf yield were higher in T4. Leaf quality viz: moisture content, total chlorophyll, crude protein, total sugar, reducing sugar and mineral in percentage (%) were significantly greater in T4. The cocoon attributes like weight of 15 larvae, single cocoon weight, shell weight, cocoon shell ratio, highest filament length, renditta and cocoon productivity/100 dfls were better also in T4 (54.68, 33.75, 0.27, 21.98, 990.41, 10.29 and 72.67) as compared to control (51.23, 31.21,0.19, 19.05, 962.96, 12.44, 69.07) respectively. Chickpea as an intercrop was given higher benefit: cost (1.30) due to increased soil fertility, higher leaf yield (except control), leaf quality, cocoon yield and additional income as compared with other intercrops (1.14, 1.07, 1.01, 0.93 and 0.86 for pea, grasspea, mugbean, sole mulberry and lentil respectively).Bangladesh J. Agri. 2022, 47(2): 107-118